Role of backwater effects on the attenuation of metal spreading in rivers: A study in the Paraopeba River after the B1 tailings dam collapse in Brumadinho - Lima, Victor Hugo Sarrazin; Pacheco, Fernando António Leal; Moura, João Paulo; Pissarra, Teresa Cristina Tarlé [UNESP]; do Valle Junior, Renato Farias; de Melo Silva, Maytê Maria Abreu Pires; Valera, Carlos Alberto; de Melo, Marília Carvalho; Sanches Fernandes, Luís Filipe (Elsevier, 2024)
The B1 tailings dam of Córrego do Feijão iron-ore mine of Vale SA, located in the Ferro-Carvão stream watershed (Brumadinho municipality, state of Minas Gerais, Brazil), collapsed in 25 January 2019. This accident had unprecedent water resources management impacts in the Paraopeba River basin, the parent of Ferro-Carvão stream, marked by the suspension of drinking water supply to the Metropolitan Region of Belo Horizonte, which was decided after the huge rise of turbidity and metal concentrations in the aquatic environment, mostly iron and manganese. The water authorities keep the use of Paraopeba River downstream of B1 dam site prohibited today, and entailed a number of studies to understand and predict the evolution of metal spreading before envisaging any suspension lift. One of those studies is presented now and had the purpose to assess the role of a weir located in the Paraopeba River and 40 km downstream from the Ferro-Carvão stream outlet, in the attenuation of iron and manganese fluxes. The weir is called Igarapé and the modeling of dissolved iron and manganese using the RiverFlow 2D software revealed a 33.5-fold attenuation of iron fluxes per unit length, from 3062.0 g/yr. km upstream the weir to 91.4 g/yr. km downstream, under stream flows typical of 10-year return periods. The attenuation was related with backwater effects that reduced flow velocities in the inundated stream banks during flood events, which induced the precipitation of iron-bearing sand particles. The attenuation was not visible for manganese because the element is preferably included in silt and clay particles that were not affected by the backwater effects because of their small sizes (and hence weights). Our results corroborate previous outcomes that highlighted the capacity of Igarapé weir to retain the B1 dam tailings, decelerating their propagation downstream, and opened a time window to remove the large volume still deposited over the river bed through dredging. The monitoring and eventual treatment of the stream banks is also paramount because the backwater effects seem to be related with flooding.
Keywords: Backwater effect; Dredging; River contamination by metals; RiverFlow2D model; Tailings dam rupture; Weir